2012
DOI: 10.1016/j.mambio.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use by a Neotropical desert marsupial (Thylamys pallidior): A multi-scale approach

Abstract: a b s t r a c tIn South America, most didelphid marsupials are associated with tropical and moist forests; however, a few species are adapted to more extreme environments such as desert systems. The desert mouse opossum, Thylamys pallidior, is a small marsupial which inhabits the arid regions of South America and has the broadest distribution of the genus. The objective of this research was to assess the habitat use and selection by the desert marsupial T. pallidior considering different scales and habitat lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
(70 reference statements)
0
1
0
2
Order By: Relevance
“…musculinus, T. pallidior, Phyllotis xantophygus) use structurally simple habitats, or are indifferent to habitat complexity (G. griseoflavus, Akodon sp. ), there being less species who prefer structurally complex habitats (Akodon molinae, Salinomys delicatus) (Corbal an, 2004;Corbal an and Debandi, 2006;Tabeni and Ojeda, 2005;Ojeda and Tabeni, 2009;Albanese et al, 2011;Albanese and Ojeda, 2012;Rodríguez et al, 2012). In some cases it was observed that there was a differential use of tree strata among species; for example, in the central Monte, desert rodents use the lower more than the upper parts of trees, whereas the marsupial T. pallidior is more selective, preferring the upper parts of trees (Albanese et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…musculinus, T. pallidior, Phyllotis xantophygus) use structurally simple habitats, or are indifferent to habitat complexity (G. griseoflavus, Akodon sp. ), there being less species who prefer structurally complex habitats (Akodon molinae, Salinomys delicatus) (Corbal an, 2004;Corbal an and Debandi, 2006;Tabeni and Ojeda, 2005;Ojeda and Tabeni, 2009;Albanese et al, 2011;Albanese and Ojeda, 2012;Rodríguez et al, 2012). In some cases it was observed that there was a differential use of tree strata among species; for example, in the central Monte, desert rodents use the lower more than the upper parts of trees, whereas the marsupial T. pallidior is more selective, preferring the upper parts of trees (Albanese et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Al igual que en otras áreas de su distribución, una parte de las especies de Thylamys encontradas en Argentina presentan asociación con ambientes áridos (Albanese y Ojeda, 2012). Sin embargo, existen varios registros de estas comadrejas en otro tipo de ambientes, como es el caso de la región pampeana.…”
unclassified
“…; Burkart, Bárbaro, Sánchez y Gómez, 1999;Cabrera, 1976). En este sentido, resulta interesante que todos los registros de Thylamys en la región pampeana correspondan a individuos de T. pallidior encontrados en ambientes subhúmedos serranos, lo cual contrasta con las condiciones de aridez o subaridez presentes en otras regiones de la distribución de esta especie (Albanese y Ojeda, 2012). Estudios basados en un número suficiente de individuos serían importantes para determinar tanto su entidad taxonómica como aspectos básicos de su biología en esta región marginal de su distribución.…”
unclassified